Psychoanalytic Perspectives on the Psychological Effects of Stillbirth on Parents: A Protocol for Systematic Review and Qualitative Synthesis - Cena, Loredana; Stefana, Alberto (Frontiers in Psychology, 2020)
Introduction Despite the fact that stillbirth has a broad economic impact on health systems and society and despite the fact that the importance of appropriate psychological and social support for parents has been highlighted, there is still a lack of research exploring the intrapsychic and interpersonal dynamics and issues triggered by the experience of stillbirth. Healthcare professionals attempting to provide effective psychological support to bereaved parents who have suffered perinatal loss continue to struggle to achieve better and deeper understanding of their psychological states and processes. Psychoanalysis could play a key role in improving this situation, but the studies available are confined to journals of psychoanalysis and there is a lack of synthesis, leaving this knowledge beyond the reach of scientists from other theoretical approaches or disciplines. This protocol proposes the systematic review and qualitative synthesis of articles from journals of psychoanalysis on the psychological effects on parents of stillbirth. Methods and analysis This systematic review will follow, as far as possible, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The Psychoanalytic Electronic Publishing Archive (1999–2019), the Single Case Archive (1999–2019), and PsycINFO (1999–2019) will be used to identify relevant articles. The review will include articles reporting clinical material and/or theoretical considerations concerning parent psychological states and processes triggered by the experience of stillbirth and a meta-synthesis will be performed. Ethics and dissemination Formal ethical approval is not required for this study, as no primary data will be collected. The findings will be published in an international peer-reviewed journal.